Tetraspanins displayed in retrovirus-derived virus-like particles and their immunogenicity. Issue 13 (18th March 2016) - Soares, H.R.; Castro, R.; Tomás, H.A.; Rodrigues, A.F.; Gomes-Alves, P.; Bellier, B.; Klatzmann, D.; Carrondo, M.J.T.; Alves, P.M.; Coroadinha, A.S.
Abstract: Virus-like particles (VLPs) are a particular subset of subunit vaccines which are currently explored as safer alternatives to live attenuated or inactivated vaccines. VLPs derived from retrovirus (retroVLPs) are commonly used as scaffolds for vaccine candidates due to their ability to incorporate heterologous envelope proteins. Pseudotyping retroVLPs is however not a selective process therefore, host cellular proteins such as tetraspanins are also included in the membrane. The contribution of these host-proteins to retrovirus immunogenicity remains unclear. In this work, human cells silenced and not silenced for tetraspanin CD81 were used to produce CD81 − or CD81 + retroVLPs. We first analyzed mice immune response against human CD81. Despite effective silencing of CD81 in retroVLP producing cells, both humoral and cellular immune responses showed persistent anti-CD81 immunogenicity, suggesting cross reactivity to related antigens. We thus compared the incorporation of related tetraspanins in retroVLPs and showed that decreased CD81 incorporation in CD81 − retro-VLPs is compensated by an increased incorporation of CD9 and CD63 tetraspanins. These results highlight the dynamic nature of host-derived proteins incorporation in retroVLPs membrane, which should be considered when retrovirus-based biopharmaceuticals are produced in xenogeneic cells.